Energy efficient production in the automotive and clothing / textiles industries in South Africa - Morris, Mike (UNIDO ViennaAT, 2011)
Outlines the types of energy efficiency opportunities available to the manufacturing industry, describing the direction that global energy efficiency policy has taken, and paying specific attention to the automotive and clothing and textiles sectors. Positions South Africa's energy efficiency policy in the global context. Analyses the energy efficiency challenges driving South African industry. Concludes by discussing the policy shortcomings apparent in respect of the named industries.